Pemahaman Perizinan PIRT dan Digitalisasi Produk UMKM Desa Bletok Kabupaten Situbondo - Bambang Sri Kaloko; Lestyo Wulandari; Muhammad Zainal Roisul Amin; Adi Mulyadi (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
Bletok Village is one of the villages in Bungatan District, Situbondo Regency. The main problem in Bletok Village is the lack of understanding regarding PIRT licensing and how to perform digital marketing, as well as the low selling value of their local products. In general, products that have P-IRT licenses have a positive impact on MSME producers in Bletok Village, such as making their product to be easily marketed or distributed legally and expanding consumer reach. The purpose of this community service program is to provide solutions related to the problems faced by the people of Bletok Village, in the form of socializing the understanding of pirt licensing and the digitalization of MSME products in Bletok Village, Situbondo District. The method used is through surveys and outreach. The results obtained from this program is for the MSME community to be able to receive and comprehend information related to PIRT licensing and digital marketing.